RASSF1A Regulates Spindle Organization by Modulating Tubulin Acetylation via SIRT2 and HDAC6 in Mouse Oocytes - Jeon, Hyuk-Joon; Oh, Jeong Su (Frontiers in Cell and Developmental Biology, 2020)
Dynamic changes in microtubules during cell cycle progression are essential for spindle organization to ensure proper segregation of chromosomes. There is growing evidence that post translational modifications of tubulins are the key factors that contribute to microtubule dynamics. However, how dynamic properties of microtubules are regulated in mouse oocytes is unclear. Here, we show that tumor suppressor RASSF1A is required for tubulin acetylation by regulating SIRT2 and HDAC6 during meiotic maturation in mouse oocytes. We found that RASSF1A was localized at the spindle microtubules in mouse oocytes. Knockdown of RASSF1A perturbed meiotic progression by impairing spindle organization and chromosome alignment. Moreover, RASSF1A knockdown disrupted kinetochore-microtubule (kMT) attachment, which activated spindle assembly checkpoint and increased the incidence of aneuploidy. In addition, RASSF1A knockdown decreased tubulin acetylation by increasing SIRT2 and HDAC6 levels. Notably, defects in spindle organization and chromosome alignment after RASSF1A knockdown were rescued not only by inhibiting SIRT2 or HDAC6 activity, but also by overexpressing acetylation mimicking K40Q tubulin. Therefore, our results demonstrated that RASSF1A regulates SIRT2- and HDAC6-mediated tubulin acetylation for proper spindle organization during oocyte meiotic maturation.